Comparison of sodium and potassium values in arterial and venous blood samples - M Mikun; K Sivakumar; Prabha Thangaraj; R Thamarai (MGM Journal of Medical Sciences)
Background: In routine practice, electrolytes are measured in serum using an electrolyte analyzer, which takes approximately 30 min. In contrast, electrolyte measurements from arterial blood using an arterial blood gas (ABG) analyzer can be completed within 5–10 min. However, limited information compares electrolyte values between venous and arterial samples. This study aims to determine if sodium (Na) and potassium (K) test results from arterial blood and venous serum samples can be used interchangeably.